Factors Related to Environmental Sanitation in Peunaga Baro Preparation Village, Meureubo, District of West Aceh - Zakiyuddin Zakiyuddin; Fitriani Fitriani; Yarmaliza Yarmaliza; Teungku Nih Farisni; Fitrah Reynaldi; Ihsan Murdani (Universitas Teuku Umar, 2020)
Environmental sanitation prioritizes prevention of environmental factors in such a way that disease emerges can be avoided. The sanitation business can also mean an effort to reduce the number of germs found in the environment so that the health status of humans is maintained perfectly. The impact of poor environmental sanitation is that it can cause the transmission of several infectious diseases, namely diarrhea, cholera, typhoid fever, and paratyphoid fever, dysentery, hookworm disease, ascariasis, hepatitis A and E, skin diseases, trachoma, schistosomiasis, cryptosporidiosis, malnutrition, and diseases associated with malnutrition. The number of people in Peunaga Baro Village in 2018 was 3,799 people, the male population was 1,984 and the female population was 1,815 with 1,102 families. The number of houses is 960 houses where the houses that meet the health requirements are 76 houses and the remaining 884 houses do not meet the health requirements. The cleanliness facilities in this village are public toilets, 3 units of drilling wells, and 4 units of landfills. Objective: to determine the factors related to environmental sanitation in the Peunaga Baro preparation village (Tzuchi Budha housing complex), Meureubo district, West Aceh district. The research method is an analytical survey with a cross sectional approach. The study was conducted from 27 November to 13 December 2019, with a population of 1,102 households and a sample of 92 households. Result: there is an action relationship P value = 0.000 and PR = 2.870, there is no relationship between income P value = 0.131 and PR = 1.838, there is a relationship between the availability of facilities P value = 0.001 and PR = 1.943 and the environment P value = 0.000 and PR = 4.139 environment sanitation. Conclusion: there is an action relationship, there is no income relationship, there is a relationship between availability and the environment with environmental sanitation. Suggestion: to the West Aceh Sanitation Office to provide a garbage dump in the Peunaga Baro Preparation Village, Meureubo District, West Aceh Regency so that and carry out regular waste transportation so that people do not litter.